Artificial intelligent modeling and optimization of the application of aluminum oxide nanoparticles modified cement asphalt toward non‐polluted sustainable environment. (26th September 2022) - Jia, Jianli; Zandi, Yousef; Agdas, Alireza Sadighi; Al‐Tamimi, Haneen M.; Banaeipour, Ali; Assilzadeh, Hamid; Elhosiny Ali, Haitham; Algarni, Hamed; Khadimallah, Mohamed Amine; Jan, Amin
Summary: Due to their excellent physicochemical and structural characteristics, aluminum oxide (AL2 O3 ) nanoparticles (AlNPs), a family of metal oxide nanoparticles, offer a variety of biological uses. Bitumen binds a high percentage (>95%) of inorganic macrometer‐sized particles to provide a cohesive material suitable for use in road pavement. In this study, AL2 O3 was added to bitumen as a new bitumen modification to improve the fatigue and rutting performance of bitumen or the base cement asphalt cement (AC) at ratios of 5, 7, and 10% wt by weight of the cement AC. Rheological tests were performed on modified bitumen containing nanoparticles. An extreme learning machine (ELM) analyzes each test outcome. In this case, the properties of AC are greatly affected by the rise in AL2 O3 concentration. In comparison to the basic AC, the modified AC's viscosity rose by 90 and 104%, respectively. The outcomes also demonstrated the excellent compatibility and storage stability of both modifiers at high temperatures. A hot mix of AL2 O3 modified bitumen was utilized to produce hot cement asphalt samples, and moisture susceptibility was assessed. As a result, the optimal nanoparticle content was chosen, and 7% AL2 O3 produced the best results. Abstract : Application of aluminum oxide nanoparticles modified cement asphalt